Is a 'Both/and' Approach to Integration Possible? A Practice Reflection on Working with Children in Out‐of‐Home Care and Their Caregivers. Issue 1 (26th February 2022) - Reid, Katherine
Abstract : The prevalence and complexity of children's mental health concerns is increasing for children living in out‐of‐home‐care settings in Australia and in other Western countries. Therapists face an amplified challenge of finding innovative ways of working with children and their caregivers, often drawing upon multiple therapeutic approaches to respond to such complexity. This article discusses some tensions of integration in practice. A case example is offered to demonstrate a way of enacting integration with Deanne, a six‐year girl, and her foster family. These practice reflections illustrate a certain way of doing a 'both‐and' approach to integration, drawing on narrative therapy and attachment therapeutic lenses. The reflections on practice reveal how a nuanced and reflexive approach to integration is needed to ensure theoretical congruence, to avoid contradictory therapeutic stances of 'knowing' and 'not‐knowing.'